Effects on profits and risks of hedging hogs in the futures market - McCoy, J.H.; Price, R.V.; Solomon, R.E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Erratic hog prices in recent years have compounded management problems. As a result, interest has increased in ways of tying down prices before the hogs are ready for market. This report presents results of a study of one approach to the problem -- hedging in the futures market.
Swine Day '76 is known as Swine Day, 1976
Keywords: Swine; Profits; Hedging; Futures markets